A Review of Metaverse - Jain, Deepak (Indian Journal of Computer Science, 2023)
The Metaverse is an evolution of the internet. It is a virtual reality simulation that can be used for various purposes, from entertainment and social networking to education and business. The present paper discusses how Metaverse can be accessed, its uses in various industries, and the technologies required for it. The paper also presents the challenges for Metaverse.